Association between depression and epigenetic age acceleration: A co‐twin control study. Issue 12 (27th June 2022) - Liu, Chang; Wang, Zeyuan; Hui, Qin; Goldberg, Jack; Smith, Nicholas L.; Shah, Amit J.; Murrah, Nancy; Shallenberger, Lucy; Diggers, Emily; Bremner, James Douglas; Sun, Yan V.; Vaccarino, Viola
Abstract: Introduction: Prior studies have shown inconsistent findings of an association between depression and epigenetic aging. DNA methylation (DNAm) age acceleration can measure biological aging. We adopted a robust co‐twin control study design to examine whether depression is associated with DNAm age acceleration after accounting for the potential confounding influences of genetics and family environment. Methods: We analyzed data on a sub‐cohort of the Vietnam Era Twin Registry. A total of 291 twins participated at baseline and 177 at follow‐up visit after a mean of 11.7 years, with 111 participants having DNA samples for both time points. Depression was measured using the Beck Depression Inventory II (BDI‐II). Six measures of DNAm age acceleration were computed at each time point, including Horvath's DNAm age acceleration (HorvathAA), intrinsic epigenetic age acceleration (IEAA), Hannum's DNAm age acceleration (HannumAA), extrinsic epigenetic age acceleration (EEAA), GrimAge acceleration (GrimAA), and PhenoAge acceleration (PhenoAA). Mixed‐effects modeling was used to assess the within‐pair association between depression and DNAm age acceleration. Results: At baseline, a 10‐unit higher BDI‐II total score was associated with HannumAA (0.73 years, 95% confidence interval [CI] 0.13–1.33, p = .019) and EEAA (0.94 years, 95% CI 0.22–1.66, p = .012). At follow‐up, 10‐unit higher BDI‐II score was associated with PhenoAA (1.32 years, 95% CI 0.18–2.47, p = .027). Conclusion: We identified that depression is associated with higher levels of DNAm age acceleration. Further investigation is warranted to better understand the underlying mechanisms for the potential causal relationship between depression and accelerated aging.